THE RISE OF CHINA: CASE STUDY BELT AND ROAD INITIATIVE IN INDONESIA - Ifatari, Ellysia Nur; Risman, Helda (PEOPLE: International Journal of Social Sciences, 2020)
The Belt and Road Initiative (BRI) is a grand strategy used by China to expand and strengthen its influence in the international sphere. In spreading BRI, China established strategic partnerships with middle and minor power countries through infrastructure development, such as the construction of an Asia-Europe silk train route, construction of an oil and gas pipeline through Central Asia-China, also a high-technology seaport in China and its destination countries. China also forming a Foreign Direct Investment (FDI) for Asian countries named the Asian Infrastructure Investment Bank (AIIB). China’s aggressiveness is increasingly visible through its one-sided effort on claiming the South China Sea. BRI has a long-term negative financial impact in the economic and trade sectors which could be seen in some African countries. However, BRI has a significant short-term impact, especially in improving the country's infrastructure sector and the development of national growth. In Indonesia, the BRI project has been approved by the government to become an alternative that supports Indonesia’s infrastructure development. BRI has been applied in Indonesia on railway construction and also power and steel industries. Furthermore, Indonesia is trying to stabilize the Asia-Pacific Region by setting its condition as the first move. This study will be analyzed using hegemonic stability theory and rational choice theory. The method used is a case study method related to the findings in this study aimed at analyzing the reasons and impacts of Indonesia choosing and establishing strategic partnerships with China amid the turmoil of the Chinese and American trade wars. Indonesia's choice of establishing strategic partnerships with China could appear as a security dilemma that Indonesia faces regarding the Asia-Pacific regional stability.